Integrating Maqashid al-Sharia, Fiqh al-Bi’ah, and Islamic Ethics for Sustainable Water Management: A Case Study of Indonesia - Hamdi, Fahmi; Ladraa, Kamel; Benjammour, Mounir; Hafidzi, Anwar; Ilhami, Hamidi (Al-Ahkam: Jurnal Ilmu Syari’ah dan Hukum, 2025)
Water resource management is a critical component of environmental sustainability, directly influencing the availability and quality of water for human consumption and ecological systems. Indonesia, as the world's largest Muslim-majority country, faces significant water management challenges, including resource mismanagement, inefficient water systems, and weak institutional framework. However, this study is unique as it develops the comprehensive Sharia-based framework for water governance in Indonesia, integrating Islamic principles particularly Maqashid al-Sharia (Islamic legal objectives) and Fiqh al-Bi'ah (Islamic environmental jurisprudence), as well as Islamic ethics into water resource management to achieve sustainability. Using a normative-juridical and interdisciplinary qualitative approach, the research analyzes Islamic texts, legal documents, environmental data, and expert opinions through content and comparative analysis. The findings reveal that Indonesia’s Water Quality Index (WQI) slightly improved from 53.88 in 2022 to 54.59 in 2023, yet water pollution persisted in 11,019 villages/sub-districts as of 2024, with Central Java being the most affected (1,366 cases). The integrated Islamic framework emphasizes the preservation of life, intellect, wealth, progeny, and religion, aligned with the principles of maslahah (public interest), ‘adl (justice), and khalifah (stewardship). This model offers both normative direction and practical solutions for policymakers, religious authorities, and environmental institutions to address water-related challenges through an ethical and faith-based lens.